INVESTIGATION ON SOME FACTORS CONTROLLING THE SORPTION OF HEAVY METALS ON ARIAKE CLAY - Y. J. Du; S. Hayashi (Lowland Technology International, 2005)
Sorption of contaminant is one of the key mechanisms in controlling transport of contaminant in clay barrier. In this study, the potential sorption of heavy metals on Ariake clay, which is a typical Japanese marine clay, is examined. Two types of heavy metals, Cd2+ and Pb2+, were selected as key contaminants and series of batch tests were performed for investigating factors controlling the sorption of Cd2+ and Pb2+ on Ariake clay. The batch test results show that the sorption of Cd2+ and Pb2+ on the Ariake clay arrived at an equilibrium condition less than the contact time prescribed by the ASTM and US EPA standards. It is found that the sorption was significantly controlled by the solid: solution ratio. With the increase in the solid: solution ratio, the sorption of Cd2+ decreased. The batch test results show that the sorption of Cd2+ increased with the increase in the pH of solution. The influence of pH on the sorption was found to be solid: solution-dependent. At relatively lower solid: solution ratio, the sorption of Cd2+ increased with increasing pH, whereas it marginally increased at relatively higher solid: solution ratio. It is concluded that the solid: solution ratio could be the crucial factor for controlling the sorption of heavy metals on the Ariake clay.